EXPERIENCE OF LEGISLATION BASIS FORMATION OF THE USA NATIONAL INNOVATION SYSTEM - A. Frolov (Russian Journal of Economics and Law)
The author touches upon one of the aspects of the USA national innovation system - formation and significance of its legislative base. The main legislation initiatives (at federal legislation level) are reviewed, their influence upon American innovation system is analyzed.